School-related anxiety symptomatology in a community sample of primary-school-aged children on the autism spectrum. (October 2018) - Adams, Dawn; Simpson, Kate; Keen, Deb
Abstract: Although it is recognized that the prevalence of anxiety is elevated in children with autism spectrum disorder, there has been very limited research exploring such anxiety in school contexts. As a result, there is limited detailed information for teachers or educators on how anxiety in autism may present in the school setting for children on the autism spectrum. The aims of this study were to (a) report the profile of results on a measure of school anxiety in a community sample of children on the autism spectrum, (b) investigate whether scores on this measure differed with child variables or enrollment into a mainstream or special school, and (c) document the level of agreement between teacher-reported and parent-reported anxiety symptoms. Teachers of 92 children aged 5–12 completed a questionnaire pack including the School Anxiety Scale-Teacher Rating (SAS-TR). Elevated levels of anxiety (above the SAS-TR total anxiety clinical cut-off) were noted in 21.7% of the sample, with a larger proportion of children scoring above the generalized anxiety cut-off (27.2%) than the social anxiety cut-off (14.1%). Older participants ( U = 744, p = .02, η 2 = 0.06) and those attending mainstream schools ( U = 661, p = .02, η 2 = 0.06) had significantly higher scores on the generalized, but not the social, anxiety subscales, with effect sizes suggesting a medium effect. The results highlight the need for further, more detailed research into the presentation and impact of school anxiety in children with autism attending both mainstream and special schools.